2015
DOI: 10.1111/jog.12876
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin inhibits oxidative stress via the activation of nuclear factor erythroid 2‐related factor 2 signaling in trophoblast cells

Abstract: Hypoxia is one of the important negative regulators of Nrf2 activation, and simvastatin inhibits oxidative stress through the activation of Nrf2 signaling in trophoblasts, indicating the potential therapeutic role of statin for pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Indeed, HMOX1 expression is decreased in placentas with preeclampsia (Chigusa et al, ) and in hypoxia‐induced trophoblasts (Ahmed et al, ). Furthermore, lower HMOX1 abundance is associated with lower cell motility and invasiveness (Bilban et al, ), whereas increasing its expression amended oxidative stress injuries in trophoblasts (Chigusa et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, HMOX1 expression is decreased in placentas with preeclampsia (Chigusa et al, ) and in hypoxia‐induced trophoblasts (Ahmed et al, ). Furthermore, lower HMOX1 abundance is associated with lower cell motility and invasiveness (Bilban et al, ), whereas increasing its expression amended oxidative stress injuries in trophoblasts (Chigusa et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that antioxidant ursodeoxycholic acid prevents acute aortic dissection via activation of Nrf2 and Nrf2-regulated antioxidant redox enzymes in aortic VSMC [ 12 ]. Furthermore, Nrf2 activation that leads to the higher expression of HMOX1 is regulated by oxidative stress and can be augmented by therapeutic agents such as statins [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Simvastatin may be a more potent inhibitor of sFlt-1 secretion from endothelial cells, trophoblast cells, and placenta from women with preterm preeclampsia than either pravastatin or rosuvastatin (24). In a human cell line (Human choriocarcinoma JAR cells), simvastatin reduces oxidative stress, which is the reason it can potentially play a role in the treatment of preeclampsia (25). Simvastatin treatment significantly decreased hypertension, sFlt-1, TNF-α, and oxidative stress marker malondialdehyde levels in a preeclampsia rat model (NG-nitro-L-arginine methyl ester-induced) (26).…”
Section: Choice Of Pravastatinmentioning
confidence: 99%